Optimization of process conditions for lipase production from rice bran by solid-state fermentation - Nur Adila Ahmad (School of Bioprocess Engineering, University Malaysia Perlis, 2013)
Lipases have potential application in different field of natural science. this study describes the production of lipases by solid - state fermentation by utilizing rice bran. Rice bran was used as the substrate for screening two funguses that is Aspergillus niger and Rhizopous oligosporus and also defined suitable incubation time for lipase production by solid - state fermentation. The best producer, Rhizopous oligosporous, was used for optimizing the process parameters for enzyme production for 6 days. The effects of the experimental variables on lipase activity had been optimized by using central composite design (CCD). Interactions were studied for three different conditions that is initial pH, temperature and moisture content for fermentation. Fermentation was then carried out under optimized conditions to obtain the lipase activity using lipase assay. Fermentation with 65 % initial moisture content and pH 6.5 of mineral media at temperature 35 oc for 6 days was found to be optimum for enzymes secretion by the fermenting organism that is 0.1753 U/mL. Biomass estimation also determined after fermentation to show growth profile for Rhizopous oligosporus. the growth profile showed that day six is the optimum growth for Rhizopous oligosporus where after day six the growth is slowly decreased. For validation of experiment, the suggested value for initial pH is 6.48, temperature is 36.68 oc and moisture content is 64.9 %. the lipases activity for validation of experiment is 0.162676 U/mL.